2015
DOI: 10.1074/jbc.m114.602086
|View full text |Cite
|
Sign up to set email alerts
|

Selective Homo- and Heteromer Interactions between the Multiple Organellar RNA Editing Factor (MORF) Proteins in Arabidopsis thaliana

Abstract: Background: RNA editing in plant organelles requires at least one of nine MORF proteins. Results: MORF proteins connect in specific homo-and heteromeric protein-protein interactions. Conclusion:The observed homo-and heteromeric combinations of MORF proteins explain why full editing can require two MORFs but one MORF can sustain basal editing levels. Significance: These findings will help to better understand RNA editing in plant organelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 40 publications
0
55
1
Order By: Relevance
“…Disruption of single-polypeptide RNA editing factors like in the moss Physcomitrella (Schallenberg-R€ udinger & may have occurred independently or may be yet another synapomorphy of the HT clade. We found no evidence in A. agrestis, however, for additional, non-PPR 'helper' components identified in angiosperms, such as MORFs/RIPs indicative of more complex editosomes (Bentolila et al, 2012;Takenaka et al, 2012;Zehrmann et al, 2015;Bayer-Cs asz ar et al, 2017;Haag et al, 2017).…”
Section: New Phytologistcontrasting
confidence: 79%
See 1 more Smart Citation
“…Disruption of single-polypeptide RNA editing factors like in the moss Physcomitrella (Schallenberg-R€ udinger & may have occurred independently or may be yet another synapomorphy of the HT clade. We found no evidence in A. agrestis, however, for additional, non-PPR 'helper' components identified in angiosperms, such as MORFs/RIPs indicative of more complex editosomes (Bentolila et al, 2012;Takenaka et al, 2012;Zehrmann et al, 2015;Bayer-Cs asz ar et al, 2017;Haag et al, 2017).…”
Section: New Phytologistcontrasting
confidence: 79%
“…However, the setup of organelle RNA editing is evidently more complex in flowering plants, where truncated proteins require interactions with DYW domains supplied in trans, frequently mediated by extra helper proteins (e.g. NUWA and multiple organellar RNA editing factor (MORF)/RNA-editing factor interacting protein (RIP) proteins) in much more complex editosomes (Takenaka et al, 2012;Bentolila et al, 2012;Boussardon et al, 2012;Sun et al, 2013Sun et al, , 2015Sun et al, , 2016Zehrmann et al, 2015;Diaz et al, 2017;Bayer-Cs asz ar et al, 2017;Andr es-Col as et al, 2017;Guillaumot et al, 2017;Sandoval et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…RNA editing in plastids and mitochondria in higher plants requires PPR proteins for site recognition and proteins of the multiple organellar RNA editing factor (MORF) family as cofactors (Zehrmann et al ., ). Our Y2H, BiFC and Co‐IP assays demonstrated that WSP1 (a MORF family member) could interact with DUA1.…”
Section: Discussionmentioning
confidence: 97%
“…7B). The large overlap of mitochondrial sites controlled by RIP1 and RIP3 is supported by a physical interaction between these two proteins, as demonstrated by yeast two-hybrid (Y2H), pulldown, and bimolecular fluorescence complementation (BiFC) assays (Zehrmann et al, 2015).…”
Section: Orrm4 Interacts With Rip1mentioning
confidence: 99%